2019
DOI: 10.3390/agronomy9020043
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone-Mediated Stomatal Response, Escape and Quiescence Strategies in Plants under Flooding Stress

Abstract: Generally, flooding causes waterlogging or submergence stress which is considered as one of the most important abiotic factors that severely hinders plant growth and development. Plants might not complete their life cycle even in short duration of flooding. As biologically intelligent organisms, plants always try to resist or survive under such adverse circumstances by adapting a wide array of mechanisms including hormonal homeostasis. Under this mechanism, plants try to adapt through diverse morphological, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…Reports show that high salt stress accumulates ABA (abscisic acid) in various plants [97], such as Arabidopsis [98] and maize [99]. Thus we speculate, sugar beet plants may accumulate ABA which induces stomatal closure and leads to lower Gs and E under osmotic stress conditions [100,101]. Lower transpiration rate leads to a compromised value of WUE [102].…”
Section: Discussionmentioning
confidence: 81%
“…Reports show that high salt stress accumulates ABA (abscisic acid) in various plants [97], such as Arabidopsis [98] and maize [99]. Thus we speculate, sugar beet plants may accumulate ABA which induces stomatal closure and leads to lower Gs and E under osmotic stress conditions [100,101]. Lower transpiration rate leads to a compromised value of WUE [102].…”
Section: Discussionmentioning
confidence: 81%
“…Since g s is responsive to almost all external and internal factors related to stress factors, it represents a highly integrative basis for the overall effect of waterlogging on photosynthetic parameters [9,22]. Previous research on g s reactions could be due to hypoxia stress-induced responses related to ethylene production which possibly caused stomatal closure [23,24,25]. The WUE, estimated by calculating A /g s , showed a decreasing quadratic trend in both waterlogged and non-waterlogged treated plants as g s increased and peaked roughly around the g s value of 0.37 mol·m −2 ·s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is no previous study on ACC deaminase-producing fungal endophytes for growth promotion and WS alleviation through bio-reduction of ET in wheat. WS can influence the molecular and biochemical prospects of plant growth and lead to morphological and physiological irregularities in plants ( Rauf et al, 2013b ; Bashar et al, 2019 ). It is reported that various endophytic fungi can act as external factories of phytohormones, enzymes, and secondary metabolites and therefore have an impact on growth attributes of respective mutant such as GA-deficient rice mutant ( Waito-C rice ) ( Sturz et al, 2000 ; Guo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%